STRATEGI MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA DINI MELALUI VIDEO COCOMELON DI ALMIRA DAYCARE PALEMBANG - Febra Mayora Choirun’nisa; Indah Dwi Sartika; Tutut Handayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Language acquisition during the golden age is a crucial stage, yet many children aged two to three still experience difficulties in articulating their thoughts. This study aims to evaluate the use of Cocomelon videos as a pedagogical strategy to improve speaking skills at Almira Daycare Palembang. The focus of the problem is directed at the effectiveness of audio-visual stimulation on expanding vocabulary and sentence structure in toddlers. This study applies a qualitative descriptive method involving five child subjects, the head of the foundation, educators, and parents. The research stages include systematic observation, in-depth interviews, and authentic documentation analyzed through data reduction and presentation techniques. The research findings indicate that the animated characters and songs in Cocomelon can stimulate children's interest in imitating sounds and words spontaneously. The results of identification of the five subjects revealed that three children reached the very good development category, one developed as expected, and one child required additional intensive stimulation. Teachers play a crucial role by repeating video material to build interactive and dynamic two-way communication. The main conclusion of the study confirms that the integration of educational audio-visual media is very effective as an instrument for enjoyable linguistic stimulation. This strategy successfully introduces new lexicon and increases children's speaking courage through real visualizations that are in line with the cognitive development of toddlers in the current preschool educational environment in Palembang city. ABSTRAK Pemerolehan bahasa pada masa keemasan merupakan tahapan krusial, namun banyak anak usia dua hingga tiga tahun masih mengalami hambatan dalam mengartikulasikan pikiran. Penelitian ini bertujuan mengevaluasi penggunaan video Cocomelon sebagai strategi pedagogis untuk meningkatkan kecakapan berbicara di Almira Daycare Palembang. Fokus masalah diarahkan pada efektivitas rangsangan audio-visual terhadap perluasan kosakata dan struktur kalimat balita. Studi ini menerapkan metode deskriptif kualitatif dengan melibatkan lima subjek anak, kepala yayasan, pendidik, dan orang tua. Tahapan penelitian mencakup observasi sistematis, wawancara mendalam, serta dokumentasi autentik yang dianalisis melalui teknik reduksi dan penyajian data. Temuan riset menunjukkan bahwa karakter animasi dan lagu dalam Cocomelon mampu memicu ketertarikan anak untuk meniru bunyi serta kata secara spontan. Hasil identifikasi pada lima subjek mengungkapkan bahwa tiga anak mencapai kategori berkembang sangat baik, satu berkembang sesuai harapan, dan satu anak memerlukan stimulasi tambahan secara intensif. Guru berperan penting dengan mengulangi materi video untuk membangun komunikasi dua arah yang interaktif dan dinamis. Simpulan utama penelitian menegaskan bahwa integrasi media audio-visual yang bersifat edukatif sangat efektif sebagai instrumen stimulasi linguistik yang menyenangkan. Strategi ini berhasil memperkenalkan leksikon baru dan meningkatkan keberanian berbicara anak melalui visualisasi nyata yang selaras dengan perkembangan kognitif balita di lingkungan pendidikan prasekolah di kota Palembang saat ini.